DESIGN OF REMOTE ANIMAL TRACKING SYSTEM USING APRS NETWORK - Thong , Noah Tsin Wee (IRC, 2020)
Animal Conservationism efforts such as animal tracking and population counting utilizing technologies has a varied history since WW2, with various technologies augmenting these efforts with the advancement of the Sciences. However the increasing complexity of such technologies has increased the barriers needed to overcome in order to use them. The recent growth in the past two decades of APRS (Automatic Packet Reporting System) in the field of Amateur Radio and in simple and modular microcontrollers such as Arduino however has opened a notable avenue of pursuit. This project strives to combine these two technologies together to seek the possibility of utilizing it for animal conservationist activities in the Malaysian rainforest.